Network intelligence standards, open source and industry research - Lingli DENG; Ninglun GU; Xiangyang YUAN; Li YU; Junlan FENG; Chao DENG; Zhiqiang YANG; Tongxu ZHANG; Rongyu WU; Xinpeng ZHANG (Dianxin kexue)
Network intelligence is the deep integration of AI technology and communication network hardware, software, systems, processes, etc.to improve process intelligence, reduce costs, increase efficiency, improve quality, accelerate technology innovation, and enable service agility.The autonomous network proposes to optimize user experience, automate management operations, and maximize resource efficiency by simplifying the network architecture, encapsulating autonomous domains, and providing closed loops for business/network operation control, which clarifies the target architecture and implementation path for network intelligence.Firstly, based on the layered architecture and evaluation framework of the autonomous network, the network intelligent technology system was summerized.Secondly, extensive research on relevant standards organizations, open source communities, industrial collaboration, and R＆amp;D and application status were conducted.Finally, gap analysis, collaborative suggestions and summary prospects for guiding the following-up industry development were provided in terms of the application requirements from operators in related practices.